SCINTIGRAPHY WITH 123I-METAIODBENZILGUANIDINE IN EVALUATION OF SYMPATHETIC INNERVATION OF THE LEFT VENTRICULAR IN PATIENTS WITH CORONARY HEART DISEASE AND ATRIAL FIBRILLATION - Yu. B. Lishmanov; S. M. Minin; I. Yu. Yefimova; Yu. V. Saushkina; I. V. Kisteneva (Бюллетень сибирской медицины)
The aim of this study was assessment of cardiac sympathetic activity in patients with atrial fibrillation by planar scintigraphy with 123I-metaIodbenzilguanidine (123I-MIBG).Material and Methods. The study included 28 (average age (57.4 ± 11.6) years) patients with suspected coronary artery disease. All patients to divide 3 groups: 13 patients (group 1) with paroxysmal AF (PAF),6 patients (group 2) with long-standing persistent AF (LSPAF) and 10 patients with no signs of AF (group 3).Planar imaging was performed to study initial (imaging started 20 minutes after MIBG injection 148 MBq 123I-MIBG) and delayed (imaging started 4 hours after 123I-MIBG injection). For the anterior planar 123I-MIBG images, regions of interest were constructed for the heart and upper mediastinum, and the heart-mediastinal ratio (HMR).Results. The delayed HMR in patients with PAF and LSPAF was significantly lower compared that in patients third group (1.59 ± 0.16, 1.54 ± 0.17 and 1.82 ± 0.11 respectively, p < 0.05). The washout rate of 123I-MIBG in patients with PAF and LSPAF was significantly highest compared that in patients with no signs of AF (33.4 ± 17.5, 29 ± 11.7 and 17.2 ± 9.6 respectively, p < 0.05). In assessment of regional sympathetic activity in patients with LSPAF defect accumulation 123I-MIBG in both the early and delayed scintigrams was significantly higher compared with groups of patients with PAF and without AF.Results of this study indicated, that the patients with atrial fibrillation has of regional LV myocardial changes, according with 123I-MIBG imaging. More sympathetic innervation abnormality was observed in patients with long-standing persistent AF.